Pengaruh Model Discovery Learning Berbantuan “Kuba-Kusa” Terhadap Hasil Belajar Matematika Siswa Kelas V - Rilfa Indah Rhadita; Wahyu Nugroho; Angga Setiawan (Jurnal Riset Madrasah Ibtidaiyah, 2022)
The purpose of this study was to determine whether the discovery learning model assisted by the "Cuban-Kusa" teaching aid had an effect on mathematics learning outcomes, especially on the volume of cubes and blocks for fifth-grade students at SDN 1 Duren. The sample of this research is the fifth-grade students at SDN 1 Duren as many as 14 students and the fifth-grade students at SDN 1 Dermosari as many as 13 students. The research method uses quantitative research, and the type of research is a non-equivalent pretest and posttest control group design. Mathematics learning outcomes are measured by a test instrument in the form of 20 multiple-choice questions. Based on the research results from hypothesis testing using an independent sample t-test, the results obtained are sig. (2-tailed) namely (0.003 < 0.05), so the results show that Ha is accepted and H0 is rejected. It can be concluded that the mathematics learning outcomes of students at SDN 1 Duren are influenced by the discovery learning model assisted by the "Cuban-Kusa" teaching aids. It can be seen from the average posttest results of 80.00 in the experimental class and the average results of 66.92 in the control class.